EVALUATION OF HOUSEHOLD WASTE MANAGEMENT IN OTOMONA VILLAGE, MIMIKA BARU DISTRICT, TIMIKA CITY - Pangestika, Elsa Widiya; Sabir, Muh (APPS Publications, 2023)
This study aims to evaluate community expectations and the performance of the Otomona Village government in managing household waste in Otomona Village, Mimika Baru District, Timika City, by looking at the variables of waste storage, waste collection and waste segregation. The method used is descriptive method. Data collection techniques used in this study are observation, questionnaires, and documentation. To evaluate household waste management, the data analysis instrument used is Importance Performance Analysis (IPA), so that the Otomona Village needs to evaluate the existence of large, large volume, and strong waste containers and placed in strategic places. Apart from that, it is necessary to distinguish between organic and inorganic waste containers for waste storage, and the Otomona Village also needs to hold a routine cooperation schedule in every area. The results depict a high-level awareness about waste management among the community dwellers in the village.